A structural investigation of heteroleptic lanthanide substituted cyclopentadienyl complexes12. (19th May 2015) - Ortu, Fabrizio; Fowler, Jonathan M.; Burton, Matthew; Formanuik, Alasdair; Mills, David P.
Abstract : The synthesis and structural authentication of novel heteroleptic lanthanide complexes supported by bulky cyclopentadienyl ligands is herein presented. Steric effects play a fundamental role in the coordination motifs. Abstract : The substituted cyclopentadienyl group 1 transfer agents KCp′′, KCp′′′ and KCp tt (Cp′′ = C5 H3 (SiMe3 )2 -1, 3 − ; Cp′′′ = C5 H2 (SiMe3 )3 -1, 2, 4 − ; Cp tt = C5 H3 ( t Bu)2 -1, 3 − ) were prepared by modification of established procedures and the structure of [K(Cp′′)(THF)]∞ ·THF (1 ) was obtained. KCp′′ and KCp tt were reacted variously with [Ln(I)3 (THF)4 ] (Ln = La, Ce) in 2 : 1 stoichiometries to afford monomeric [La(Cp′′)2 (I)(THF)] (2a·THF ) and the dimeric complexes [La(Cp′′)2 (μ-I)]2 (2a ), [Ce(Cp′′)2 (μ-I)]2 (2b ) and [Ce(Cp tt )2 (μ-I)]2 (3 ). KCp′′′ was reacted with [Ce(I)3 (THF)4 ] to afford the mono-ring complex [Ce(Cp′′′)(I)2 (THF)2 ] (4 ), regardless of the stoichiometric ratio of the reagents. Complex4 was reacted with [KN(SiMe3 )2 ] to yield [Ce(Cp′′′)2 (I)(THF)] (5 ), [Ce(Cp′′′)N(SiMe3 )2 2 ] (6 ) and [CeN(SiMe3 )2 3 ] by ligand scrambling. Complexes1–6 have all been structurally authenticated and are variously characterised by other physical methods.